Alexithymia and estimated 10-year cardiovascular disease risk in healthy adults: a community-based cross-sectional study - Vadini, Francesco; Lanzara, Roberta; Iuliani, Ornella; Affaitati, Gianna Pia; Porcelli, Piero (Frontiers in Psychology, 2024)
Background: This cohort study aimed to explore whether and to what extent alexithymia would be associated with cardiovascular disease (CVD) risk over an estimated 10-year period, over and above established clinical cofactors (i.e., depressive symptoms, quality of life, sociodemographic, anthropometric, lifestyle, and biological data), in a low-risk population of blood donors. Methods: A sample of 1,021 adult Italian blood donors (age 46.9±8.39; 61.2% men) was consecutively recruited. The 10-year-CVD risk score was estimated using the CUORE risk score (CRS). Sociodemographic, lifestyle, anthropometric, biological, and psychological (i.e., quality of life, depressive symptoms, and alexithymia) CVD risk data were assessed using validated self‐report measures or clinical records. Results: As expected, most participants (78.5%) had a low CVD risk (CRS<3%) and an overall low-risk profile for all the parameters. Compared with subjects at low risk of CVD (n=911, 78.5%), those with high risk (i.e. rated ≥3 on CUORE risk assessment; n=250, 21.5%) reported higher levels of alexithymia (p<.001). Subjects with higher alexithymia (n=236, 23.1%) reported higher levels of psychosocial impairment, depressive symptoms, and biological risk variables for CVD. Alexithymia was significantly associated with 10-year CVD risk (OR=1.02, 95% CI=1.01-1.04, p=.009), even after adjusting for key sociodemographic and clinical risk variables. Conclusion: Although limited by the cross-sectional design, this study is the first to show that alexithymia leads to a higher risk for 10-year CVD estimate in healthy subjects with low-risk profile, regardless of known biomarkers and traditional CVD risk factors.